Platynosomum fastosum em felinos domésticos em Cuiabá, região Centro-Oeste do Brasil - Lima, Raissa Lopes (2021)
Platynosomum fastosum has distribution in tropical and subtropical regions and is the main parasite in the biliary system of domestic cats. Cats can be asymptomatic or show severe signs of cholangitis. In Brazil the infection is reported throughout the territory, but in the Midwest region of the country, there are only post-mortem studies. Therefore, the objective of this research was to research the frequency of parasitism by P. fastosum in domestic cats treated at the Veterinary Hospital of the Federal University of Mato Grosso, campus Cuiabá, associating clinical and laboratory changes (blood count, biochemistry, and ultrasound) with different coproparasitological techniques (formalin-ether sedimentation, Faust and Hoffmann). One hundred and seventy-one cats were evaluated clinically and laboratorially and a semi-structured epidemiological questionnaire was applied to the tutors. The prevalence observed was 26.90%, with no significant association with gender, reproductive status, age, hunting habit, access to the street and recent anthelmintic treatment and the guardian's lack of knowledge regarding parasitism. Of the evaluated cats, 55 (32.16%, p <0.01) showed clinical signs suggestive of cholangitis with a significant association of this variable. Regarding the clinical pathological variables, mild neutrophilia and non-significant elevation in serum ALT and FA activity were observed, while the mean values of eosinophils, total leukocytes, total protein, albumin, and globulin were normal. The ultrasound findings were like those already described, dilated bile ducts, thickened gallbladder, enlarged liver and gallbladder sediment. P. fastosum parasitism occurred in approximately one quarter (26.90%) of the cats in the sample evaluated in Cuiabá-MT, with a significant association with the clinical signs of cholangitis and regular agreement between the coproparasitological techniques employed.